THE GRAY WOLF STALEMATE: WHY UTAH’S WOLF MANAGEMENT LAW THREATENS THE GRAY WOLF’S RECOVERY THROUGHOUT ITS HISTORICAL RANGE (Utah Environmental Law Review; Vol 32 No 1 (2012))
800x600 Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} This Note intends to show that Utah's complete prohibition of wolves within the state, which is a significant portion of the gray wolf's historical and current range, makes the state unready to manage the wolves under federal statutory and regulatory guidelines. By contrast, the neighboring states of Montana, Idaho, and Washington are committed to managing at least fifteen packs, while Wyoming and Oregon committed to at least four and seven, respectively. The presence of gray wolves within Utah represents a vital component of continued gray wolf recovery, because as the gray wolf's population increases, corridors are necessary for dispersing gray wolves. While wolves were not reintroduced in Utah, Washington or Oregon-the Pacific Northwest states-have at least committed to managing and allowing dispersing wolves to establish packs and to facilitate continued recovery. In addition to the need for Utah to serve as a corridor for gray wolves, Utah has suitable habitat and was once part of the species' historical range. If court precedent rather than the 2011 Rider were followed, Utah would appropriately be considered a significant portion of the gray wolf's range, and the species could not have been delisted until Utah's regulatory mechanisms were changed to promote further recovery.